2017
DOI: 10.1136/bcr-2016-217284
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of renal angiomyolipoma during pregnancy

Abstract: A renal angiomyolipoma (AML) is a rare benign tumour of kidney origin. Pregnancy is known to be associated with an increased risk of tumour rupture causing hypovolaemic shock, which is usually managed surgically or through an embolisation procedure. However, having surgery during pregnancy predisposes the mother to a preterm delivery, and the unknown influences of radiation exposure to the fetus make the management of such cases very challenging. A 30-year-old pregnant woman had a sudden onset of gross haematu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
(2 reference statements)
0
7
0
1
Order By: Relevance
“…We also find some pregnant women who are diagnosed with renal angiomyolipoma are treated with conservative follow-up. A case was reported that a pregnant woman with a 10 cm mass suggestive of angiomyolipoma in the left kidney had a spontaneous rupture at the 20th week of her pregnancy, and the operation was performed until the 34th week [ 14 ]. It was reported that almost 75% of renal angiomyolipoma pregnant women had a risk of tumor rupture [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also find some pregnant women who are diagnosed with renal angiomyolipoma are treated with conservative follow-up. A case was reported that a pregnant woman with a 10 cm mass suggestive of angiomyolipoma in the left kidney had a spontaneous rupture at the 20th week of her pregnancy, and the operation was performed until the 34th week [ 14 ]. It was reported that almost 75% of renal angiomyolipoma pregnant women had a risk of tumor rupture [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…AML during pregnancy is characterized by faster growth, potentially invasive behaviors, and an increased risk of rupture with massive retroperitoneal hemorrhage. [ 24 , 25 ] In particular, spontaneous renal hemorrhage during pregnancy is rare but the consequences may be catastrophic, including maternal shock and intrauterine fetal death. Pregnancy exerts its negative impacts on AML in many ways.…”
Section: Risk Factors For Aml Rupturementioning
confidence: 99%
“…Bleeding may prompt emergency treatment. Conservative management and elective caesarian section were reported when the patient was asymptomatic, hemodynamically stable, or could be stabilized by blood transfusions ( 58 61 ). Treating a bleeding lesion by nephrectomy or PN may compromise the continuation of pregnancy ( 62 ).…”
Section: Risk Of Bleedingmentioning
confidence: 99%